Does labor supply modeling affect findings of transport policy analyses? - Georg Hirte; Stefan Tscharaktschiew (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2015)
The transport and urban economics literature applies different labor supply approaches when studying economic or planning instruments. Some studies assume that working hours are endogenous while the number of workdays is given, whereas others model only decisions on workdays. Unfortunately, empirical evidence does hardly exist on account of missing data. Against this background, we provide an assessment of whether general effects of transport policies are robust against the modeling of leisure demand and labor supply. We introduce different labor supply approaches into a spatial general equilibrium model and discuss how they affect the welfare implication of congestion policies. We, then, perform simulations and find that in many cases the choice of labor supply modeling not only affects the magnitude of the policy impact but also its direction. While planning instruments are suggested to be quite robust to different labor supply approaches, the way of modeling labor supply may crucially affect the overall welfare implications of economic instruments such as congestion tolls. Based on these findings it becomes clear which labor supply approach is the most appropriate given specific conditions. Our study also emphasizes the need for better micro labor market data that also feature days of sickness, overtime work used to reduce workdays, the actual number of leave days, part-time work, days with telecommuting etc.
Keywords: H2; H3; J22; Q5; R1; R4; R5; 330; Public Economics; Tax Efficiency; Time Allocation; Labor Supply; Pigouvian; Tax; Environmental Economics; Urban Economics; Spatial Economics; Regional Welfare; Land-Use; Zoning; CGE; Spatial Economics; Spatial Modeling; Transportation